Hubungan antara Penyesuaian Diri dengan Prestasi Akademik Mahasiswa - Abdullah Yunus; Gita Erwilya (Fakultas Dakwah UIN Sulthan Thaha Saifuddin Jambi, 2021)
This article is motivated by the phenomenon of new students when they start entering college, the transition from high school to university brings up various social and academic changes that will be faced by students. The purpose of this study was to determine whether there is a relationship between self-adjustment and academic achievement of students of the da'wah faculty of the State Islamic University of Sultan Thaha Saifuddin Jambi. The research method used is multiple correlation, which is the method used to determine the relationship between one variable and another. The subjects in this study were 92 students of the Da'wah Faculty for the 2019 Academic Year. Based on the results of the research analysis, the correlation results were p = 0.005 0.005. The results obtained from the data analysis are Ho is rejected and Ha is accepted, so that the results show that there is a relationship between self-adjustment and academic achievement of students of the Da'wah Faculty of Sultan Thaha Saifuddin State Islamic University Jambi.